2017
DOI: 10.7589/2016-08-192
|View full text |Cite
|
Sign up to set email alerts
|

Stress Response of Juvenile Green Sea Turtles (Chelonia mydas) with Different Fibropapillomatosis Scores

Abstract: Green sea turtles ( Chelonia mydas ) with cutaneous fibropapillomatosis (FP) occur in some populations worldwide, and the survivability of these individuals may be compromised depending on the disease severity score. Furthermore, populations may be negatively affected in areas with a high prevalence of the disease. The stress responses (corticosterone, glucose, lactate, and hematocrit) to capture and handling were assessed in animals with different FP severity scores. From 18 January 2013 to 31 July 2014, 33 j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
1
5
0
1
Order By: Relevance
“…Approximately 41% of individuals that stranded in the study area alive or as reasonably preserved carcasses showed external FP tumors, which is generally consistent with previous FP prevalence estimates for the study area [18,28,[33][34][35]. However, because of the different methods used to survey FP prevalence over the years (beach surveys, intentional capture and dive surveys), it is not possible to ascertain the historical trends of this disease in the study area.…”
Section: Factors Determining the Presence Or Absence Of Fp Tumors (Da...supporting
confidence: 81%
See 2 more Smart Citations
“…Approximately 41% of individuals that stranded in the study area alive or as reasonably preserved carcasses showed external FP tumors, which is generally consistent with previous FP prevalence estimates for the study area [18,28,[33][34][35]. However, because of the different methods used to survey FP prevalence over the years (beach surveys, intentional capture and dive surveys), it is not possible to ascertain the historical trends of this disease in the study area.…”
Section: Factors Determining the Presence Or Absence Of Fp Tumors (Da...supporting
confidence: 81%
“…The overall prevalence of FP in green turtles in Espı ´rito Santo was estimated at 27.4% [28]. Warm water effluent discharge from metallurgical (iron ore/steel) plants is known to attract aggregations of juvenile green turtles in this area, and underwater surveys have reported average FP prevalence between 34.4% and 75.8% at these sites [18,[33][34][35]. At least two closely-related ChHV5 variants occur in juvenile green turtles with FP in Espı ´rito Santo, both of which are similar to those that circulate in the South Atlantic Ocean but are distinct from the variants found in the Caribbean and Pacific Ocean [44].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Turtles were captured by hand by an experienced swimmer following the technique described by Limpus (1978) and brought onboard. On the boat we recorded curved carapace length (CCL), notch to tip, with a flexible measuring tape (Bolten 1999) and, considering external physical evaluation (sensu Santos et al 2017), the number, size, anatomic region, gross morphology, consistency, and color of cutaneous tumors present on each animal. Tumor size was recorded with a digital caliper, measuring the longest axis (Rossi et al 2016).…”
mentioning
confidence: 99%
“…Las tortugas fueron atrapadas manualmente por un nadador experimentado siguiendo la técnica descrita por Limpus (1978) y, posteriormente, fueron subidas a bordo. En la embarcación, se midió el largo curvo del caparazón (LCC) con una cinta métrica flexible (Bolten 1999) y, con base en la evaluación física externa (sensu Santos et al 2017), se registró el número, el tamaño, la región anatómica, la morfología, la consistencia y el color de los tumores cutáneos presentes en cada animal. El tamaño de los tumores se obtuvo usando un vernier digital midiendo el eje mayor (Rossi et al 2016).…”
unclassified